Evidence-based violence risk assessment in psychiatric inpatient care: an implementation study - Lantta, Tella (Annales Universitatis Turkuensis D 1255, 2016)
The aim of this study was to promote evidence-based violence risk assessment in inpatient psychiatric care. The study was an implementation study with three phases utilizing a mixed-method approach. The Ottawa Model of Research Use was used as a theoretical framework. The setting was three closed adults’ psychiatric wards and two associations for families of mental health patients. The violence risk assessment intervention implemented was the Dynamic Appraisal of Situational Aggression. First, assessment of key elements for implementation was explored from the perspectives of nursing staff, relatives of mental health patients, and the practice environment. In addition, the intervention was specified. Second, implementation was monitored on the wards: barriers and facilitators for the implementation, knowledge transfer strategies, adaptation and use of the intervention were explored. Third, evaluation of outcomes of the intervention implemented was done from perspectives of nursing staff and mental health inpatients. The feasibility of the intervention was explored. Assessment of key elements revealed the views of nursing staffs and relatives of mental health patients on the complexity of violent events in psychiatric care and identified common needs for the development of violence prevention and management. Monitoring the implementation yielded knowledge about intervention implementation in the clinical practice setting and its challenges. Evaluation of implementation outcomes revealed mixed perceptions of violence risk assessment intervention and the feasibility criteria set were not fully met. This dissertation provides new insights which can be utilized when implementing novel methods to prevent and manage patent violence in more user-centered manners. On basis of the study results, patient involvement in short-term risk assessment can be seen as a new, promising working method in psychiatric inpatient care. Thus, to confirm this finding, more research is needed.

Näyttöön perustuva väkivallan riskinarvointi psykiatrisessa sairaalahoidossa: implementointi-tutkimus Tutkimuksen tavoitteena oli edistää näyttöön perustuvaa väkivallan riskinarviointia psykiatrisessa sairaalahoidossa. Tutkimus toteutettiin implementointitutkimuksena hyödyntäen monimenetelmällisyyttä ja se jakautui kolmeen vaiheeseen Ottawa Model of Research Use viitekehyksen mukaisesti. Tutkimusympäristönä olivat kolme suljettua aikuispsykiatrista osastoa ja kaksi mielenterveysomaisten järjestöä. Tutkimuksessa käytäntöön viety väkivallan riskinarviointimenetelmä oli Dynamic Appraisal of Situational Aggression. Ensimmäisessä vaiheessa arvioitiin hoitohenkilökunnan, mielenterveysomaisten ja käytännön työympäristön näkökulmasta tärkeimpiä tekijöitä uuden menetelmän käytäntöön viemisen suhteen. Käytäntöön vietävä menetelmä tarkennettiin. Toisessa vaiheessa intervention käytäntöön viemistä seurattiin osastoilla: Käytäntöön viemistä estävät ja edistävät tekijät tunnistettiin. Strategiat menetelmän käytäntöön viemiseksi valittiin. Menetelmän käyttöönottoa seurattiin. Kolmannessa vaiheessa hoitohenkilökunta ja potilaat arvioivat käytäntöön viedyn menetelmän, sekä menetelmän käyttökelpoisuutta tutkittiin. Tutkimuksen tulosten mukaan uuden menetelmän käytäntöön viemisen tärkeimpinä huomioitavina tekijöitä olivat hoitajien ja mielenterveysomaisten näkökulmista väkivaltatilanteiden kompleksisuus psykiatrisessa hoidossa. Yhteisiä tarpeita väkivallan ennaltaehkäisemisen ja hallitsemisen kehittämiseksi löydettiin. Tulokset toivat tietoa menetelmien käytäntöön viemisen menetelmistä käytännön työympäristöissä ja siihen liittyvistä haasteista. Näkemykset käytäntöön viedystä väkivallan riskinarviointimenetelmästä olivat ristiriitaiset eivätkä asetetut kriteerit menetelmän käyttökelpoisuudesta täyttyneet täysin. Tämä väitöskirja tuottaa uutta tietoa, jota voidaan hyödyntää vietäessä käytäntöön uusia käyttäjälähtöisiä menetelmiä potilasväkivallan ennaltaehkäisemiseksi ja hallitsemiseksi. Potilaiden mukaanottoa väkivallan lyhyen aikavälin riskinarviointiin voidaan pitää tulosten perusteella uutena, lupaavana lähestymistapana psykiatrisessa sairaalahoidossa. Lisätutkimusta tarvitaan kuitenkin havainnon vahvistamiseksi.